2020
DOI: 10.1596/33165
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging ICT Technologies in Closing the Gender Gap

Abstract: In recent decades, the growth of information and communications technologies (ICT) and the move toward the digitalization of trade and global value chains has been radically transforming the global trade scene, with important implications for women engaged in trade. In order to identify adequate measures to reduce gender disparities, this paper reviews and discusses evidence from the existing literature, as well as presents evidence from a number of new empirical analyses. It also introduces two new frameworks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
13
1
1
Order By: Relevance
“…This could be because of change in socio-cultural environment owing to technological changes. Technology has helped in reducing the gender gap (Sicat et al, 2020) which has been supported by the results of H4-H6.…”
Section: Findings and Discussionmentioning
confidence: 66%
“…This could be because of change in socio-cultural environment owing to technological changes. Technology has helped in reducing the gender gap (Sicat et al, 2020) which has been supported by the results of H4-H6.…”
Section: Findings and Discussionmentioning
confidence: 66%
“…On the other hand, it has also been found that there was no difference observed in the subgroup analysis to find out the difference in gender in the process of OL adoption, which implied that the BI adoption for OL for both males and females is equal in the HEI. Technology has significantly reduced the gender gap (Sicat et al ., 2020). In an OL scenario, Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…DiCaprio and Suominen (2015) conducted a survey of Pacific Island exporters and found that a higher concentration of female executives in firms were active online. Sicat et al (2020) explored e-commerce trade from a gender perspective. Through an examination of case studies, they found that female entrepreneurs are more active than men in selling and buying products online.…”
Section: Digitalization and Gender Participation In The Labor Marketmentioning
confidence: 99%
“…In addition, digitalization of trade and global value chains has fundamentally changed the landscape of globalization, with important implications for women as traders and employees (Sicat et al, 2020). Theoretically, the interaction of digitalization and globalization can narrow or widen the gender gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation